A Systematic Review of the Challenges in Teaching Programming for Primary Schools’ Students - Salleh Hudin, Salmiah (Online Journal for TVET Practitioners, 2023)
Programming and coding in primary education become solicitude globally today. Governments all over the world agreed on the importance of education towards workforce empowerment in the future for the country's development. As primary education is the foundation to produce future human resources, the government decided to make curricular changes starting with young learners.  The schooling system tries to adapt to the rapid changes caused by The Industrial Revolution 4.0 by introducing programming education at an early stage. The increased usage of automation, robots, and artificial intelligence in the industry nowadays makes people aware of the importance of mastering programming and coding skill to survive in their future careers. Through the learning process of programming and coding, young students start to be exposed to computational skill which involves critical thinking and imagining creatively. Programming and coding education promote computational thinking for young learners which includes problem-solving skills like deconstruction, abstraction, pattern recognition, and algorithms.  This paper examines research exploring the challenges faced by teachers, students, facilities, parents, and the government in the implementation of programming education in primary schools. The exploration was done through a systematic literature review of 20 articles published between the years 2018 and 2022. The selection of 20 articles required is based on the PRISMA guidelines to select papers by Moher et al. (2009). The findings provide insight into what has and has not been studied across a range of literature and the alignment with the broader context of programming education at the primary level. From this study, it can be identified that teachers’ competency, teachers’ digital pedagogy, students’ readiness, school facilities, parents’ support, and government educational planning play a very important role to make programming education for young learners successful.